Inkar al-Sunnah di Era Digital: Tantangan dan Strategi Multidimensional Pendidikan Islam - Tatu Nurkamilah; Romlah Abubakar Askar; Suparta Suparta (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
The rapid development of digital technology has transformed the dissemination and consumption of religious information among Muslim communities. Alongside these advancements, the spread of Inkār al-Sunnah ideology through digital platforms has become a significant challenge to the integrity of Islamic religious understanding, particularly among younger generations who are frequently exposed to unverified religious content. This phenomenon has the potential to weaken the authority of the Sunnah as a primary source of Islamic teachings alongside the Qur'an. This study aims to examine Islamic education strategies in countering the spread of Inkār al-Sunnah in the digital era, focusing on strengthening hadith literacy, enhancing the role of Islamic Education teachers, utilizing digital media, and developing religious moderation education. The research employs a qualitative approach through library research and content analysis of relevant academic literature. The findings indicate that the challenge of Inkār al-Sunnah affects three dimensions of Islamic education: curricular, pedagogical, and socio-digital. In response, a multidimensional strategy is required, including strengthening Islamic epistemology, improving hadith literacy, contextualising learning through the living hadith approach, reformulating hadith curricula, optimizing educational digital media, enhancing teacher competencies, strengthening Islamic educational institutions, fostering family-school collaboration, and promoting religious moderation education. The study concludes that adaptive and integrative Islamic education, grounded in the Qur'an and Sunnah, plays a crucial role in developing a generation of Muslims who are critical, knowledgeable, digitally literate, and moderate in responding to contemporary religious challenges in the digital age.